2011
DOI: 10.1158/0008-5472.can-10-1588
|View full text |Cite
|
Sign up to set email alerts
|

hTERT Overexpression Alleviates Intracellular ROS Production, Improves Mitochondrial Function, and Inhibits ROS-Mediated Apoptosis in Cancer Cells

Abstract: The human telomerase reverse transcriptase (hTERT) is the catalytic subunit of the telomerase holoenzyme. Evidence is accumulating to link hTERT to activities other than telomere maintenance and immortalization. Here, we show that hTERT overexpression not only reduces the basal cellular reactive oxygen species (ROS) levels but also inhibits endogenous ROS production in response to stimuli that induce intracellular ROS generation. Conversely, siRNA-mediated gene silencing of hTERT potentiated the increase in ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
194
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(203 citation statements)
references
References 49 publications
(53 reference statements)
9
194
0
Order By: Relevance
“…This investigation also showed that the antioxidant function of TERT may be linked to an increase in the ratio of reduced glutathione to oxidized glutathione in addition to an improved recovery of the peroxiredoxin in its reduced state. As a substantiation of the previous results we mentioned earlier, the authors of this study were able to show that TERT induces an increase in complex IV activity (cytochrome c oxidase) (Indran et al, 2011). In the meantime it was also confirmed that these cells overexpressing TERT display a higher resistance to H2O2-induced apoptosis.…”
Section: Tert Oxidative Stress and Mitochondriasupporting
confidence: 91%
See 3 more Smart Citations
“…This investigation also showed that the antioxidant function of TERT may be linked to an increase in the ratio of reduced glutathione to oxidized glutathione in addition to an improved recovery of the peroxiredoxin in its reduced state. As a substantiation of the previous results we mentioned earlier, the authors of this study were able to show that TERT induces an increase in complex IV activity (cytochrome c oxidase) (Indran et al, 2011). In the meantime it was also confirmed that these cells overexpressing TERT display a higher resistance to H2O2-induced apoptosis.…”
Section: Tert Oxidative Stress and Mitochondriasupporting
confidence: 91%
“…Another recent report also confirmed the role of TERT as a modulator of ROS production (Indran et al, 2010(Indran et al, , 2011. Indeed it was observed that TERT overexpression induces reduction of basal levels of ROS and inhibits the ROS production induced by oxidative stress (Figure 2).…”
Section: Tert Oxidative Stress and Mitochondriasupporting
confidence: 57%
See 2 more Smart Citations
“…Thus, the results of the present study indicate that 23,24-dihydrocucurbitacin B may induce apoptosis by increasing intracellular ROS and decreasing the ΔΨm. Several anticancer drugs act against cancer by producing ROS (21,22); for example, afferent A disrupts the ΔΨm and induces oxidative stress, ultimately inducing apoptosis in osteosarcoma cells (23).…”
Section: Discussionmentioning
confidence: 99%